Sustainable iron-based oxygen carriers for Chemical Looping for Hydrogen Generation. (15th January 2019) - De Vos, Yoran; Jacobs, Marijke; Van Der Voort, Pascal; Van Driessche, Isabel; Snijkers, Frans; Verberckmoes, An
Abstract: We report a detailed reactor study of two sustainable Fe-based oxygen carriers (OC) prepared by spray drying. We compare Fe2 O3 supported on Al2 O3 and MgFeAlOx in isothermal Chemical Looping for Hydrogen Generation. In this process, CH4 is converted into syngas (H2 + CO) and H2 O is used as the oxidant that reduces to pure H2 . We noticed that the Al2 O3 supported OC deactivates quickly while the MgFeAlOx supported OC withstands >60 cycles. We will show that the irreversible formation of an inactive FeAl2 O4 phase is responsible for the deactivation of the alumina supported OC. We show detailed information on all the transient stages of the process and the different crystalline forms that are created, and combine this information into a full chemical looping cycle for both OC. Moreover, we evaluate the crushing strength of the oxygen carriers within a full chemical looping cycle and during long-term operation and we investigated the conversion of H2 O and the selectivity to H2 -production during long-term oxygen carrier regeneration. The MgFeAlOx support with an extra Fe-based active phase is a promising material to replace the typical Ni-based oxygen carriers, as it forms a sustainable non-toxic, stable and green alternative for hydrogen generation by chemical looping. Graphical abstract: Highlights: Active phase-support interactions vital for long-term viability. Al2 O3 -supported oxygen carrier deactivate under successive steam regeneration. MgFeAlOx -supports are partially regenerable by steam during hydrogen production. MgFeAlOx-supports display stable chemical looping for up to 60 cycles. Repeated cycling enhances microstructure and activates MgFeAlOx -supported carriers.